Eleven new heteroscleromorph Demospongiae (Porifera), and a new record of the tetractinellid Ancorina corticata, from Walters Shoal, a shallow seamount on the Madagascar Ridge in the South West Indian Ocean (SWIO) - Payne, Robyn P.; Samaai, Toufiek; Janson, Liesl; Kerwath, Sven E.; Gibbons, Mark J. (Zootaxa, 2025)
Walters Shoal is a shallow seamount located on the South Madagascar Ridge, which is situated approximately 833 km south of Madagascar and 1,296 km east of South Africa. Even though it penetrates the euphotic zone (summit is 15 m below the sea surface) and is protected by the Southern Indian Ocean Deep-Sea Fishers Association, there is a paucity of biodiversity and oceanographic data. Thus, a multidisciplinary cruise was initiated in May 2014 on the FRS Algoa as a component of the African Coelacanth Ecosystem Programme (III). This paper reports on 11 new heteroscleromorph Demospongiae collected from Walters Shoal, namely Chelotropella alexrogersi sp. nov., Penares waltershoalensis sp. nov., Tethya muricyi sp. nov., Agelas kellyae sp. nov., Ptilocaulis ramosus sp. nov., Halichondria (Halichondria) madagascarensis sp. nov., Aaptos incrustans sp. nov., Lissodendoryx (Lissodendoryx) ingolei sp. nov., Fibulia punicea sp. nov., Clathria (Clathria) flo sp. nov. and Callyspongia (Callyspongia) cacumen sp. nov. Additionally, a range extension of Ancorina corticata Lévi, 1964, is reported. The sponge assemblage had high levels of endemism with several species shared by both the western and eastern flanks of the seamount. In contrast, sponge assemblages differed significantly according to depth, with the mesophotic zone (31–150 m) acting as a transition between the shallow (15–30 m) and submesophotic (> 150 m) zones. Species richness and the number of new species were highest in the submesophotic zone.